Atomization of liquids by disintegrating thin liquid films using gas jets. (January 2017) - Mezhericher, Maksim; Ladizhensky, Izhak; Etlin, Isaac
Highlights: A new method of liquid atomization into submicron droplets has been invented. The method includes production and disintegration of thin liquid films by gas jets. Tap water droplets with Sauter diameters 2.66–7.53 µm were produced in experiments. Formation of bubbles, froth and "micro-sprays" of droplets was directly observed. The new method is scalable, simple and low cost, and suitable for different liquids. Abstract: Liquid atomization is useful in many applications, such as engineering, science, pharmaceutics, medicine, forensics and others. In the present research, an innovative methodology and a new device for atomization of liquids into mists of micron and submicron droplets have been developed. The new liquid-atomization method exploits the physical phenomenon of fragmentation of thin liquid films into fine micron and submicron droplets by gas jets. For several tested prototypes, the direct observations using a high-speed visualization technique have demonstrated that bubbles were generated within a liquid and their shells have been subsequently destroyed by applying a mechanical impulse (pressure of a compressed air) once the bubbles came over the liquid surface. The main characteristics of the generated tap water mists have been experimentally measured by means of the laser diffraction technique under various conditions for each prototype. One of the prototype devices allowed obtaining mists containing 90–99% of droplets smaller than 1 µm, with the minimum arithmetic and Sauter mean droplet diameters of 1.48 µm and 2.66 µm, and the 2.64 ml/min of droplet flow rate for 3.5 bar manometer pressure of atomizing air. The gas to liquid mass ratios (GLR) in the new device are depending on the atomizing tube length and the number of perforated orifices in the tube: more the tube length, hence more the number of perforated orifices, and therefore more liquid droplets will form for the same gas flow rate. The measured GLR values related to 1 m length of the utilized atomizing tube were in the range of 0.65–1.06, and for the specifically utilized atomizing tube of 72 mm length were among 9.07–14.67. The results of this study demonstrate that the developed method of generation of very fine droplet mists has many advantages over the existing techniques and can be perspective for many practical applications. Graphical abstract: